2015
DOI: 10.18632/oncotarget.6351
|View full text |Cite
|
Sign up to set email alerts
|

SUV420H1 enhances the phosphorylation and transcription of ERK1 in cancer cells

Abstract: The oncogenic protein ERK, a member of the extracellular signal-regulated kinase (ERK) cascade, is a well characterized signaling molecule involved in tumorigenesis. The ERK signaling pathway is activated in a large proportion of cancers and plays a critical role in tumor development. Functional regulation by phosphorylation of kinases in the ERK pathway has been extensively studied, however methylation of the ERK protein has not been reported to date. Here, we demonstrated that the protein lysine methyltransf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 50 publications
(32 reference statements)
0
41
1
Order By: Relevance
“…1c). Quantitative analysis of these results revealed that SUV4-20H1 exhibits 10 fold more activity on monomethylated (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) arrays containing unmethylated (me0) and mono-methylated (me1) lysine 20 and a mutant peptide (K20 A) by SUV4-20H1 and SUV4-20H2 (incubation times 60 min in each case). The autoradiography image indicates the transfer of the radioactively labeled methyl groups to the peptides.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…1c). Quantitative analysis of these results revealed that SUV4-20H1 exhibits 10 fold more activity on monomethylated (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) arrays containing unmethylated (me0) and mono-methylated (me1) lysine 20 and a mutant peptide (K20 A) by SUV4-20H1 and SUV4-20H2 (incubation times 60 min in each case). The autoradiography image indicates the transfer of the radioactively labeled methyl groups to the peptides.…”
Section: Resultsmentioning
confidence: 98%
“…We, therefore, aimed to test the activity of these proteins on H4 peptide substrates with different methylation states of K20. 15 amino acid long peptides with the sequence of the H4 tail (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) containing K20 at the center were synthesized on cellulose membrane using the SPOT synthesis method [28]. SPOT-arrays containing different forms of H4K20 (H4K20me1, H4K20me0 and H4K20A) peptides were methylated with SUV4-20H proteins using radioactively labeled [methyl-3 H]-AdoMet as a cofactor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the decades of studies of ERK1/2 phosphorylation, especially at the Thr202/Tyr204 sites in ERK1 and Thr185/Tyr187 in ERK2 of the Thr-X-Tyr motif, the studies of other PTMs of ERK1/2, including acetylation, methylation, and ubiquitination, are just emerging. Recently, two lysine sites at the ERK1 C-terminus, Lys302 and Lys361, have been revealed to be tri-methylated, and methylation of ERK1 enhances its phosphorylation (17). Arg309 of ERK1 has also been reported as a methylation site via a proteome-wide analysis, yet the function of this site is not clear (18).…”
mentioning
confidence: 99%